Studying teachers in early childhood settings - Saracho, Olivia N.; Spodek, Bernard (Contemporary perspectives in early childhood education., 2003)
The chapters in this volume reflect the impact that teachers have on their students when "they stand in front of the classroom" and the effect their performance have on children such as teachers gender, preparation, certification, knowledge, beliefs, cognitive style, creativity, accountability, and other actions on the part of the teachers. They describe research related to the preparation and certification or credentialing of early childhood practitioners, the issues regarding the nature of early childhood practice, and the needs of the field as it prepares for the future.